Trismus in patients with head and neck cancer: etiopathogenesis, diagnosis and management. (December 2015) - Rapidis, A.D.; Dijkstra, P.U.; Roodenburg, J.L.N.; Rodrigo, J.P.; Rinaldo, A.; Strojan, P.; Takes, R.P.; Ferlito, A.
Abstract : Background: Trismus indicates severely restricted mouth opening of any aetiology. A mouth opening of 35 mm or less should be regarded as trismus. Aim of this study was to review the etiopathogenesis, incidence, treatment and prevention of trismus in patients with head and neck cancer. Objective of review: Trismus is frequently seen in patients suffering from malignant tumours of the head and neck. The reported prevalence of trismus in those patients varies considerably in the literature and ranges from 0 to 100% depending on the tumour site and extension. Trismus may worsen or remain the same over time, or the symptoms may reduce, even in the absence of treatment. When a patient presents with trismus after tumour treatment, it is important to determine whether the trismus is the result of the treatment, or is the first sign of a recurrence. Restricted mouth opening may impede inspection of the oral cavity as needed for dental care, and particularly for oncologic follow‐up. Conclusions: Mouth opening after radiotherapy (RT) decreases on average by approximately 20% compared to mouth opening prior to RT. The prevalence of trismus increases with increasing doses of RT to mastication structures. The use of intensity‐modulated RT seems to lower the percentage and severity of RT‐induced trismus. Treatment of trismus can be conservative (with either medical or physical therapy) or surgical. Exercise therapy is the mainstay of treatment and exercise should start as soon as possible after treatment. The prevention of trismus, rather than its treatment, is the most important objective.